The impact of CSR on green purchase intention: Empirical evidence from the green building Industries in Taiwan - Tao, Yi-Tien; Lin, Min-Der; Khan, Asif (Frontiers in Psychology, 2022)
Worldwide supplies are being utilized at a disturbing rate and to a significant degree, the building business has been accountable for this ecological deprivation, particularly because of its elevated level of energy expenditure. Hence, this research paper targets the customers of green building industries in Taiwan and developed a framework based on Carroll’s corporate social responsibility (CSR) model, theory of planned behavior (TPB), and cognitive consistency theory (CCT), to measure the impact of CSR on green purchase intention (GPI). Furthermore, it analyzes the impact of CSR on green word of mouth (GWOM), green attitude (GA), green concern (GC), and green trust (GT). Moreover, it explores the roles of GA, GC, GWOM, and GT on GPI. Finally, to study the mediating roles of GC, GA, and GWOM, with the relationship between CSR and GPI. As per the results of this research, CSR was discovered to have a positive impact on GPI, GWOM, GA, GC, and GT. Furthermore, GWOM had a significant impact on GPI. Moreover, GC and GT were in a significant relationship with GPI. Consequently, all the relationships were significant except the relationship between GA and GPI. Furthermore, GT, GWOM, and GC fully mediate the relationship between CSR and GPI. However, GA was not found to significantly mediate the relationship between CSR and GPI. The findings of this study provide practical implications regarding the impact of CSR on GPI and the trending issue of sustainable career development.